Improved cut flower production, rhizome dormancy breaking and feasibility study of curcuma alismatifolia gagnep. using soilless media cultivation - Chen, Xingwei (2021)
The effects of three soilless media (cocopeat: sand at 2:1 by volume, burnt rice husk: sand at 2:1 by volume and cocopeat: burnt rice husk: sand at 1:1:1 by volume) and three planting densities (9, 16 and 49 plants/m2) on the growth, flower quality and rhizome yield of Curcuma alismatifolia were investigated. Cocopeat: burnt rice husk: sand (1:1:1 by volume) produced the largest flower (8.09±0.27 cm), highest mean number of flowers per clump (2.85±0.20 stalks) and highest mean number of rhizomes per m2 (86.67±4.04 rhizomes/m2). Planting density at 16 plants/m2 produced high number of flowers per clump (2.92±0.19 stalks/clump) and high mean number of rhizomes per clump (2.95±0.67 rhizomes/clump). Although high planting density at 49 plants/m2 produced the highest cut flower yield (62.42±7.24 stalks/m2) and rhizome yield per m2 (120.92±3.94 rhizomes/m2) but the number of cut flowers per clump (1.28±0.15 stalks/clump) and rhizomes per clump (1.31±0.37 rhizomes/clump) were the lowest. The vase life, number of pink bracts, number of green bracts and flower stalk size were not affected by different types of soilless media and planting densities. The effects of storage duration (5, 10 and 15 weeks) and 6-Benzylaminopurine (BAP) application (0 and 100 mg/L) on the growth and flowering of C. alismatifolia were investigated. Rhizomes stored for 10 and 15 weeks started to germinate two weeks after planting while rhizomes stored for 5 weeks took 8 weeks to germinate regardless of the BAP treatments. Rhizome fresh weight, abscisic acid (ABA) level, starch content and total soluble sugar reduced with longer storage duration. Flower quality was not affected by storage duration and BAP treatment. Investigation on perception of consumer on flower quality and financial analysis of C. alismatifolia production in soilless trough system was carried out. C. alismatifolia flower obtained positive evaluation on its quality and rated as a very good cut flower. The highest gross profit was obtained from growing C. alismatifolia at planting density of 16 plants/m2. The positive net present value (NPV), benefit-cost ratio (BCR) at 1.03, internal rate of return (IRR) at 13% and pay back period (PP) less than 2 years indicated that C. alismatifolia production in soilless trough system at planting density of 16 plants/m2 is feasible.